PENGARUH LATIHAN SPEED PLAY TERHADAP KECEPATAN LARI PEMAIN FUTSAL SMK TARUNA MASMUR PEKANBARU - Salmi, Jefri; Zainur, Zainur; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: study aimed to analyze the effect of speed play training on the futsal player running speed of smk taruna masmur pekanbaru. The design of this study uses a group of the research is wearing the approach one group pretest-posttest design. The populations in this study are 10 students. The sampling technique is to use the total sampling, where the total population is sampled. Data collection techniques were obtained from pre-test and post test. The instrument used in this research was a 30 meter running speed test to measure running speed. The data is then statistically processed to test the normality using the lilliefors test at a significance level of 0.05a. Based on the analysis of statistical data, the data pree test Lhitung of 0,128, 1964 data post test Lhitung of 0,150 and Ltabel 0,258,then Lhitung < Ltabel. Based on data analysis pree-test and post-test there are differences in the numbers are rising or an increase of 1,73. Based on t test analysis produces Ttabel >Thitung of 86,5 and Ttabel 1,833, then Thitung>Ttabel. Thus , there is the effect of speed play training on the futsal player speed of SMK Taruna Masmur Pekanbaru.Key Words: Speed Play, Speed